Pengaruh Model Self Organized Learning Environment dan Model Kooperatif STAD terhadap Kompetensi Pengetahuan ditinjau dari Kemandirian Belajar pada Materi Fluida Dinamis - Adi Setiawan; Pujayanto Pujayanto; Ahmad Fauzi (Postgraduate, University of Mataram, 2023)
This study aims to investigate the differences in the effect of using Self-Organized Learning Environment and STAD cooperative learning models supported by the Sigil module on knowledge competency in terms of learning independence, and to investigate the differences in the effect of different categories of student learning independence on student knowledge competency. This study aim also to investigate interaction between learning independence with Self-Organized Learning Environment model and STAD cooperative learning model on student knowledge competency. The type of this research is a quasi-experiment. Using the cluster random sampling technique, class XI MIPA 1 was chosen as the experimental class, and class XI MIPA 3 as the control class. Data were collected using documentation, test, and questionnaire distribution methods. Data were analyzed using a two-way ANOVA technique followed by multiple comparison tests using Scheffe's method. The results of the study indicate that there is no difference in the effect of Self-Organized Learning Environment and STAD cooperative learning models supported by the Sigil module on students’ knowledge competency, and there is a difference in the effect between categories of student learning independence on knowledge competence. This study also proves that there is no interaction effect of the use of learning models and learning independence on knowledge competency.